(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يهدف البحث إلى الكشف عن مستوى الذكاء ونسبة انتشار الرضاعة الطبيعية والاصطناعية لدى أفراد عينة البحث, بالإضافة إلى تحديد الفروق في مستوى الذكاء بين الأطفال ذوي الرضاعة الطبيعية والأطفال ذوي الرضاعة الاصطناعية, على عينة مكونة من (260) تلميذاً وتلميذة من الصفين الثالث والسادس من مرحلة التعليم الأساسي في مدينة حمص, وذلك باستخدام اختبار رسم الرجل لـِ جودإنف. وتم التوصل إلى أن مستويات الذكاء متفاوتة بين الذكور والإناث وكانت الفروق لصالح الذكور, أما نسبة انتشار الرضاعة الطبيعية كانت أكثر من نسبة انتشار الرضاعة الاصطناعية, كما تبين عدم وجود فروق ذات دلالة إحصائية بين الأطفال ذوي الرضاعة الطبيعية والأطفال ذوي الرضاعة الاصطناعية في مستوى الذكاء عند مستوى الدلالة (0.05) The aim of this search is to detect the level of the intelligence, the spread rate of the natural and artificial breastfeeding at sample individuals, and determining the differences at the level of intelligence between the children who had natural breastfeeding and the children who had artificial breastfeeding. The sample includes (260) schoolboys and schoolgirls from the third and sixth grade, and uses the GoodEnough′s Test for man drawing. The results varied between the males and the females as to the levels of the intelligence – they were in favor of males, and the spread rate of the natural breastfeeding was more than the spread rate of the artificial breastfeeding. However, there were no differences with statistical indications between the children who had natural breastfeeding and the children who had artificial breastfeeding in the Intelligence Test at the indication level (0.05).